Negotiating Quality for Social Work: A Participatory Research Project in South Tyrol. (July 2020) - Lorenz, Walter A.; Fargion, Silvia; Nothdurfter, Urban; Nagy, Andrea; Berger, Elisabeth; Rainer, Sylvia; Frei, Sabina
Purpose: The measurement of quality in social work practice has become an area of growing interest and relevance in the social services field. Our starting point is that quality in interventions with human beings has to be defined in ways that incorporate the multiple perspectives of all the subjects involved. Methods: The study, adopting qualitative and quantitative methods, explored issues of quality in social services provision in South Tyrol in Italy from the point of view of the main stakeholders. Results: It was possible to identify four dimensions of quality that stakeholders considered important: the political role of practitioners, the ability to take an active role in the organization, the capacity to connect with other professionals, and the quality of direct relationships with users. Conclusions: Results provide an understanding of the common and differing expectations evident in stakeholders' perspectives and ideas for better quality systems